Gut microbiota is a potential goalkeeper of dyslipidemia - Lei, Lirong; Zhao, Ning; Zhang, Lei; Chen, Jiamei; Liu, Xiaomin; Piao, Shenghua (Frontiers in Endocrinology, 2022)
Dyslipidemia, as a common metabolic disease, could cause atherosclerosis, coronary heart disease, stroke and other cardio-cerebrovascular diseases. It is mainly caused by the interaction of genetic and environmental factors and its incidence has increased for several years. A large number of studies have shown that gut microbiota disorder is related to the development of dyslipidemia closely. Especially its metabolites such as short-chain fatty acids, bile acids and trimethylamine N-oxide affect dyslipidemia by regulating cholesterol balance. In this paper, we systematically reviewed the literature and used knowledge graphs to analyze the research trends and characteristics of dyslipidemia mediated by gut microbiota, revealing that the interaction between diet and gut microbiota leads to dyslipidemia as one of the main factors. In addition, starting from the destruction of the dynamic balance between gut microbiota and host caused by dyslipidemia, we systematically summarize the molecular mechanism of gut microbiota regulating dyslipidemia and provide a theoretical basis for the treatment of dyslipidemia by targeting the gut microbiota.